Status of Integrated Soil Fertility Management (ISFM) in Southwestern Nigeria - O.T, Ande; Huising, Jerome; Ojo, A. O; Azeez, J; Are, K.S; Olakojo, S.A; Fademi, I.O; Ojeniyi, S.O (International Journal of Sustainable Agricultural Research, 2017)
The soils of South western Nigeria are rapidly degrading due to nutrient mining, soil loss, inappropriate land use, low inherent soil fertility coupled with adverse effects of climate change. These have resulted to persistent low yields and farmers’ poverty. The current farming systems have failed to improve continuous decline in crop production. There is need for integrated approach that involves mineral fertilizer, organic resources, and improved crop varieties with sound agronomic practices if the region will be able to feed its population of over 35 million people. Integrated Soil Fertility Management (ISFM) is an all-encompassing resource management technique that embraces the use of good planting materials, with appropriate organic and/or inorganic fertilizer application or their integrated use. It also entails adapting the various combinations of the ISFM components to local conditions which by implication means site specific management. There is lack of coordinated information about the components of ISFM being used in SWN and most stakeholders have not appreciated the importance of integrated approach. This paper is therefore put forward to review the status of Integrated Soil Fertility Management in South western Nigeria in order to identify knowledge gap for sustainable crop production in the region.